Radon Activity in Volcanic Gases of Mt. Etna by Passive Dosimetry. Issue 9 (18th September 2020) - Terray, Luca; Gauthier, Pierre‐Jean; Breton, Vincent; Giammanco, Salvatore; Sigmarsson, Olgeir; Salerno, Giuseppe; Caltabiano, Tommaso; Falvard, Alain
Abstract: Radon ( 222 Rn) activity in air was measured for about 6 months at the summit of Mt. Etna Central Crater (Sicily) by integrative radon dosimetry at two different heights above ground level (5 cm and 1 m). This technique for air radon monitoring proved operational in the harsh volcanic environment of Mt. Etna summit with a 94% recovery rate of dosimeters. In the southeast sector exposed to the main gas plume, mean radon activity in free air (height 1 m) is significantly higher than the local background and the ground level activity (height 5 cm). The results strongly suggest that the plume is enriched in radon by ≈550 Bq/m 3, which has never been evidenced before. Radon activities also reflect soil degassing occurring in the proximity of the crater, with increased ground level activities in zones of enhanced soil fracturing and degassing. Radon measurements also revealed a hot spot in front of the Voragine vent with extraordinary high levels of air activities (26 kBq/m 3 at ground level and 8 kBq/m 3 in free air). The temporal variation of radon activity was investigated by replacing a few stations half way through the exposure period. The only significant increase was associated with the site located under the main gas plume and correlated with eruptive unrest within the crater. Finally, air radon levels higher than the recommended threshold of 300 Bq/m 3 were detected in several zones on the rim and could generate a nonnegligible radiologic dose for workers on the volcano. Key Points: First direct measurement of radon ( 222 Rn) activity in a diluted volcanic gas plume Evidence of significant radon enrichment in the magmatic vapor released at open‐conduit volcanoes Increased radon activity correlated with eruptive unrest suggests to use radon in gas plumes as a tracer of degassing kinetics